Nanoindentation mechanical properties characterization of glassy polymeric carbon treated with ion beam - Rodrigues, M. G.; da Cruz, N. C.; Rangel, E. C.; Zimmerman, R. L.; Ila, D.; Poker, D. B.; Hensley, D. K. (Elsevier B.V., 2002)
Phenolic resins when heat treated in inert atmosphere up to 1000 degreesC become glassy polymeric carbon (GPC), a chemically inert and biocompatible material useful for medical applications, such as in the manufacture of heart valves and prosthetic devices. In earlier work we have shown that ion bombardment can modify the surface of GPC, increasing its roughness. The enhanced roughness, which depends on the species, energy and fluence of the ion beam, can improve the biocompatibility of GPC prosthetic artifacts. In this work, ion bombardment was used to make a layer of implanted ions under the surface to avoid the propagation of microcracks in regions where cardiac valves should have pins for fixation of the leaflets. GPC samples prepared at 700 and 1500 degreesC were bombarded with ions of silicon. carbon, oxygen and gold at energies of 5, 6, 8 and 10 MeV, respectively, and fluences between 1.0 x 10(13) and 1.0 x 10(16) ions/cm(2). Nanoindentation hardness characterization was used to compare bombarded with non-bombarded samples prepared at temperatures up to 2500 degreesC. The results with samples not bombarded showed that the hardness of GPC increases strongly with the heat treatment temperature. Comparison with ion bombarded samples shows that the hardness changes according to the ion used, the energy and fluence. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: glassy polymeric carbon; ion beam; hardness